Characterization of Pontibacter altruii, sp. nov., isolated from a human blood culture. (September 2017) - Roiko, M.; May, M.; Relich, R.F.
Abstract: The genus Pontibacter is a recent addition to the family Cytophagaceae, phylum Bacteroidetes . Previous reports of its cultivation and molecular detection are from a variety of environmental sources, including marine and desert habitats. We report the first description of a Pontibacter sp., which was initially identified as Elizabethkingia meningoseptica, isolated from a human clinical specimen. On the basis of 16S rRNA gene sequence, unique mass spectral profile and phenotypic characterization, this isolate represents a novel species within the genus Pontibacter that has been named Pontibacter altruii, sp. nov., strain Grand Forks.